Research methodology : a step-by-step guide for beginners / Ranjit Kumar - Kumar, Ranjit
Written specifically for students with no previous experience of research and research methodology, the third edition of Research Methodology: A Step-by-Step Guide for Beginners breaks the process the process of designing and doing a research project into eight manageable steps and provides lots of examples throughout to link theory to the practice of doing research. The book contains straightforward, practical guidance on: - Formulating a research question - Ethical considerations - Carrying out a literature review - Choosing a research design - Selecting a sample - Collecting and analysing qualitative and quantitative data - Writing a research report. The third edition has been revised and updated to include extended coverage of qualitative research methods in addition to the existing comprehensive coverage of quantitative methods. There are also brand new learning features such as reflective questions throughout the text to help students consolidate their knowledge. The book is essential reading for undergraduate and postgraduate students in the social sciences embarking on qualitative or quantitative research projects